An Industrial Application of Resource-Based View of Firm in China: Identifying Core Competencies and Achieving Sustainability - Zhou, Wuzhen (2013)
This thesis attempts to explore the theory application within one China based organisation, in this way to address the void in by studying the implications of applying resource based view, core competency and dynamic capability concepts to foreign organisation business management, by identifying the core competencies and the dynamic capabilities of the company.